Definition and content of the concept of transparency of criminal justice (Law and Safety, 2022)
Common law approaches to the modern understanding of transparency in the sphere of public administration and judiciary have been considered. On the basis of the models for the definition of this concept and its content proposed in the specialized scientific literature, the author's definition of the transparency of criminal justice has been proposed. The circle of elements included in its content has been outlined, which have been also defined. Based on the provisions of the idea of judicial transparency in general, the definition has been formulated and the main features of the concept of criminal justice transparency have been outlined. Transparency of criminal justice is a principle that includes such principles of criminal court activity as transparency, openness, publicity, publicity, access to public information, accountability.On the basis of the analysis of criminal procedural norms that reveal the content of the principles of publicity and openness, suggestions have been made regarding: 1) increasing the degree of legal certainty of the norms that regulate the procedure for consideration by the investigating judge of a request for the conduct of secret investigative (search) actions; 2) it is necessary to take into account that the list of grounds provided for in Art. 27 of the Criminal Procedure Code of Ukraine, is not exhaustive, and/or to provide for the grounds indicated in this article, or to indicate that other cases provided for by the Criminal Procedure Code of Ukraine are possible. In this regard, it has been proposed to supplement Part 2 of Article 27 of the CPC of Ukraine with paragraph 6 as follows: “When the investigating judge considers the petitions of the investigator, agreed with the prosecutor, or the prosecutor to conduct covert investigative (search) actions, temporary access to things and documents (if there is a real threat of alteration or destruction of things or documents), as well as in case of need to ensure the seizure of property”; 3) the fact that the legislator, when setting out paragraph 1 of Part 2 of Article 27 of the CPC of Ukraine had not taken into account the fact that at the stage of pre-trial investigation the circumstances concerning the minor are also subject to consideration by the court, i.e. the investigating judge. Therefore, in such cases, one should talk about the expediency of protecting the personal interests of the suspect, who is already a minor, and not the accused. On the basis of the above, it has been proposed to set out paragraph 1, part 2 of Art. 27 of the Criminal Procedure Code of Ukraine in the following version: “If the accused or suspect is a minor”.
Keywords: criminal justice; transparency; clarity; openness; publicity; access to public information; accountability of the judiciary.